Financial Literacy and Retirement Planning in Nepal: The Mediating Role of Social Influence - Subedi, Dhruba Prasad; Bhandari, Dilli Ram (PYC Nepal Journal of Management, 2024)
Financial literacy provides individuals with the essential knowledge and skills to make well-informed decisions regarding their retirement plans. This study explores the impact of financial literacy on retirement planning among civil servants in Nepal, with a particular focus on the mediating role of social influence. To achieve the research objectives, primary data were collected using a structured questionnaire employing a convenience sampling method. The sample consisted of 250 civil servants, including both officer and non-officer level employees from government offices. To test the relationship between financial literacy and retirement planning with the mediating role of social influence, the descriptive and casual comparative research designs were used. Structural relationships within the proposed theoretical model were analyzed using Smart PLS 4.0. The findings reveal that financial literacy significantly influences retirement planning, and this relationship is further strengthened by the presence of social influences. The results indicate that financial literacy provides individuals with the essential knowledge and skills to make informed decisions about savings, investments, and retirement planning. These insights highlight the need of financial literacy for effective retirement planning to promote financial awareness and preparedness. This study is essential as it reveals how financial literacy empowers Nepalese civil servants to make informed retirement decisions, fostering financial security in their later years.